The scramble for African oil oppression, corruption and war for control of Africa's natural resources - Yates, Douglas A. (London Pluto Press, 2012)
Africa is often seen as a place to be pitied or feared as an area of instability. This book challenges these complacent assumptions, showing how our demand for oil contributes to the chronic problems plaguing the continent.
Includes bibliographical references (p. 239-247) and index.
Keywords: Petroleum industry and trade